2015
DOI: 10.3389/fnhum.2015.00378
|View full text |Cite
|
Sign up to set email alerts
|

Effects of informative and confirmatory feedback on brain activation during negative feedback processing

Abstract: The current study compared the effects of informative and confirmatory feedback on brain activation during negative feedback processing. For confirmatory feedback trials, participants were informed that they had failed the task, whereas informative feedback trials presented task relevant information along with the notification of their failure. Fourteen male undergraduates performed a series of spatial-perceptual tasks and received feedback while their brain activity was recorded. During confirmatory feedback … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…DlPFC is regarded as the core node of the regulatory network and is associated with motor suppression, working memory, reasoning, and complex cognition [ 12 , 53 ]. Moreover, dlPFC has an important role in top-down cognitive control [ 23 , 54 , 55 ] and explicit regulation [ 13 , 52 ]. Previous studies [ 9 , 56 58 ] have shown hypoactivation in the dlPFC in tasks of explicit reappraisal in participant samples with anxiety and mood disorders.…”
Section: Discussionmentioning
confidence: 99%
“…DlPFC is regarded as the core node of the regulatory network and is associated with motor suppression, working memory, reasoning, and complex cognition [ 12 , 53 ]. Moreover, dlPFC has an important role in top-down cognitive control [ 23 , 54 , 55 ] and explicit regulation [ 13 , 52 ]. Previous studies [ 9 , 56 58 ] have shown hypoactivation in the dlPFC in tasks of explicit reappraisal in participant samples with anxiety and mood disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Following the ideas of Darwin ( 1872 ) and James ( 1884 ) that it is the afferent signals from the body which elicit emotions and feelings, several theorists in the field of emotion have postulated that sensory feedback from facial and postural movements contribute significantly to emotional experience (Tomkins, 1962 ; Laird, 1974 ; Izard, 1993 ). Indeed, a number of studies have demonstrated that feelings and attitude are affected by changing proprioceptive input from the muscles and joints through the adoption or mimicry of a certain facial expression, (McIntosh, 1996 ; Carr et al, 2003 ; Davis et al, 2009 ), posture (Riskind and Gotay, 1982 ; Duclos et al, 1989 ; Cacioppo et al, 1993 ; Stepper and Strack, 1993 ; Neumann and Strack, 2000 ; Duclos and Laird, 2001 ; Carney et al, 2010 ), head movement (Briñol and Petty, 2003 ; Forster, 2004 ), isometric muscle contraction in the arms (Cacioppo et al, 1993 ; Neumann and Strack, 2000 ), or certain expressive whole-body movements (Duclos and Laird, 2001 ; Shafir et al, 2013 ). It has further been demonstrated that combining both facial and bodily expressions of a certain emotion has a cumulative effect, producing stronger feelings of the corresponding emotion than do either bodily or facial expression alone (Flack et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Anterior Cingulate Cortex (ACC), Dorsolateral Prefrontal Cortex (DLPFC), and the cortico-striatal circuit play an important role in the development and function of the executive system (Adleman et al, 2002). Specifically, these brain regions have been implicated in feedback processing (Ferdinand, & Opitz, 2014; Hauser et al, 2014; Holroyd, & Coles, 2002; Woo et al, 2015) and undergo considerable maturational changes from childhood into early adulthood (Adleman, et al, 2002; Casey, et al, 1997; Cunningham, Bhattacharyya, & Benes, 2002; Rubia, Smith, Taylor, & Brammer, 2007; Velanova, Wheeler, & Luna, 2008; Vijayakumar, et al, 2014). Given that feedback processing relies on developing brain regions and circuits, it is pertinent to consider it as a developing skill.…”
Section: Introductionmentioning
confidence: 99%